2016
DOI: 10.17795/zjrms-5994
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Aspects of the Predominant Species of Phlebotominae Sand Flies (Diptera: Psychodidae) in Hamadan, Iran

Abstract: Background: Leishmaniases are important diseases in many parts of the world, which are transmitted by bites of sand flies. Objectives: This study aimed at investigating some ecological aspects of sand flies in Hamadan. Materials and Methods: In this descriptive cross-sectional study, sand flies were collected weekly by sticky traps. Results: For this study, 3305 sand flies were collected and identified during 2013. Sand flies active season began from May till October in Hamadan. The greatest activity occurring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
(7 reference statements)
1
6
0
Order By: Relevance
“…The abundance of P. papatasi and absence of P. sergenti in the outskirts of Yazd may also indicate the lower tendency of P. sergenti to rodent burrows or Haloxylon (a plant that has been cultivated for reconditioning of the desert). Similar to other studies [ 6 , 11 ] which used the sticky traps to collect Phlebotominae sand flies male/female sex ratio for most species was more than one, except for P. caucasicus which was less than one. Such differences were also reported in the case of P. duboscqi in Northern Ethiopia [ 17 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The abundance of P. papatasi and absence of P. sergenti in the outskirts of Yazd may also indicate the lower tendency of P. sergenti to rodent burrows or Haloxylon (a plant that has been cultivated for reconditioning of the desert). Similar to other studies [ 6 , 11 ] which used the sticky traps to collect Phlebotominae sand flies male/female sex ratio for most species was more than one, except for P. caucasicus which was less than one. Such differences were also reported in the case of P. duboscqi in Northern Ethiopia [ 17 ].…”
Section: Discussionsupporting
confidence: 76%
“…Many studies have been conducted in the field of leishmaniasis and there is reduction in the number of reported cutaneous cases of leishmaniasis in Iran [ 3 , 4 ], but even with the great efforts of health authorities over the last four decades, there is still a considerable number of foci of disease distributed throughout the country [ 4 ]. In addition to different types of leishmaniasis, sand flies may carry a number of other viral diseases such as papatasi fever, summer meningitis, or Toscana virus as well as Carrion's disease that is caused by bacteria [ 5 , 6 ]. Similar to most other studies on arthropod borne diseases on the fauna of vectors, the distribution and other characteristics of diseases have great importance in planning any program to reduce or even stop transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that there are outbreaks of disease in areas of the country where the disease was not recorded in the past ( 23 , 24 ). It should always be remembered that due to the presence of sand flies in most parts of the province ( 8 , 9 , 11 ), the introduction of disease to clean areas is feasible. In addition, a related work has suggested that environmental variation caused by climate change could create new endemic foci in the country ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite basic information on the etiology, vectors, and method of transmission of the disease, CL continues to be a serious health problem in Iran, and in some parts of the country, the number of cases is rising ( 10 ). They are endemic in 17 out of 31 provinces of Iran ( 11 ) and the recorded number of incidences reaches 20,000 new cases every year, although the real number of affected patients is estimated to be 4 or 5 times more than this, as most cases of diseases remain unreported ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…This disease is caused by a protozoan parasite called Leishmania from the Trypanosomatidae family and Leishmania genus [3]. This disease is transmitted to humans or animals by the bite of a female insect called sandflies from the Psychodidae family [4]. Dogs and rodents are the main reservoirs of this disease [5].…”
Section: Introductionmentioning
confidence: 99%